RESILIENSI IBU BEKERJA YANG MEMILIKI ANAK DENGAN GANGGUAN PENDENGARAN - Lubuk, Frederica Ranithya; Widyawati, Yapina (MANASA, 2024)
Parents of hearing-impaired children have various challenges that can cause stress. As they work, these challenges may increase. However, they must still be able to facilitate optimal care for their child’s development, especially at the age of 5-12, because children start to enter social environments. Resilience helps individuals to survive and adapt when experiencing difficulties. Therefore, it is important for parents to have resilience which affects their psychological well-being and their children’s quality of life. The research uses qualitative methods with phenomenological design and thematic analysis. The participants are hearing mothers, who work and have one child with hearing impairment aged 5-12 years old. This research found that all three participants showed resilience after accepting their child’s condition and going through unique dynamics. Perception of stressors, understanding of children’s characteristics, coping abilities, social support, positive interpretation, spirituality, and social support, play a role. Therefore, parents can continue to learn about their child’s condition and seek social support.